OPTIMALISASI PENGATURAN PERSIMPANGAN JALAN ADYAKSA DAN JALAN CEMARA DI BANJARMASIN - Rosehan Anwar; M. Fitriansyah (Universitas Lambung Mangkurat, 2013)
At the intersection of Jl. Cemara dan Jl. Adiyaksa and often times when the vehicles must always stop for a red signal minimal get two times that cause get a long delay. This study aimed to obtain the most excellent service of several alternatives. Intersection analysis method MKJI. With the help of the program exsel to simplify the calculation. conclusions as follows: Level intersection performance Jl. Adhiyaksa – Jl. Sultan Adam - Jl. Cemara Raya – Jl. Cemara Raya 2 Banjarmasin for current conditions (Existing) with 4 phases can in category high degree of saturation. Intersection flow ratio of 0.718, the cycle time of 88 seconds, the average delay across the intersection 84 seconds. For the Service Level Index (ITP) obtained Service Level F.From the analysis of the field data (Existing conditions) with a new design (the condition settings) from some of the alternatives, then get that degree of saturation is smaller and Service Level, using traffic flow arrangement Phase 3 (of 3 alternative design results)